2015
DOI: 10.1007/s10055-015-0270-8
|View full text |Cite
|
Sign up to set email alerts
|

On the validity of virtual reality-based auditory experiments: a case study about ratings of the overall listening experience

Abstract: In recent years, new developments have led to an increasing number of virtual reality (VR)-based experiments, but little is known about their validity compared to real-world experiments. To this end, an experiment was carried out which compares responses given in a real-world environment to responses given in a VR environment. In the experiment, thirty participants rated the overall listening experience of music excerpts while sitting in a cinema and a listening booth being in a real-world environment and in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Few studies used simulation-based auralizations presented via headphones and compared speech intelligibility in this setup with the one measured in the real rooms, e.g. [20,21,22], or overall listening experience [23]. One early study compared speech intelligibility in a loudspeaker-based auralization system and in a real room using binaural ACTA ACUSTICA UNITED WITH ACUSTICA Vol.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies used simulation-based auralizations presented via headphones and compared speech intelligibility in this setup with the one measured in the real rooms, e.g. [20,21,22], or overall listening experience [23]. One early study compared speech intelligibility in a loudspeaker-based auralization system and in a real room using binaural ACTA ACUSTICA UNITED WITH ACUSTICA Vol.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, participants are allowed to involve affective aspects, like emotional or individual aspects. Typically, five-star Likert scales are utilized in this type of evaluation, since they are known to lead to consistent ratings [14,15]. The method comprises two phases: In the first phase, participants rate stimuli that (if possible) have not been processed by any audio system under test in a multi-stimulus procedure.…”
Section: Likert Scale/evaluation Of Overall Listening Experiencementioning
confidence: 99%
“…For further discussions on the choice of question when assessing OLE please refer to Schoeffler [22] (pp. [35][36][37][38][39][40][41][42].…”
Section: Procedures Of Listening Sessionsmentioning
confidence: 99%
“…The choice of analysis for Likert-type data is well discussed in the literature and some prominent studies such as [37] advocate the use of either non-parametric or parametric analysis. Specific to the analysis of OLE, it was shown that there are only minor differences in effect sizes and statistical significance values when comparing non-parametric and parametric methods [38]. In the analysis of the OLE data presented here, the data are predominantly regarded as ordinal and as such non-parametric statistical techniques are used.…”
Section: Ole Analysismentioning
confidence: 99%